Trajectory Models of Deep Bed Filtration - Riyad Al-Anbai; Mahdi Essa; Afrah Al- Ithari (Engineering and Technology Journal, 2005)
In this research an analysis and evaluation is made to five of the trajectory models. These five models were chosen among the others because they represent the new approach in modeling filtration process. The five trajectory models which were analyzed and evaluated are: 1 O'Melia and Ali model (1978). 2. Tien et al. model (1979). 3. Chiang and Tien model (1985). 4 Mackie et al. model (1987). 5. Choo and Tien model (1993). Comparisons between the predicted values from these trajectory models with the experimental data taken from the work of Chiang (1985), Tanaka (1982), and Mohammed (1989) were made.